Plasma proteomics analysis of Chinese HIV-1 infected individuals focusing on the immune and inflammatory factors afford insight into the viral control mechanism - Ni, Wanqi; Ren, Li; Liao, Lingjie; Li, Dan; Luo, Zhenwu; Zhu, Meiling; Liu, Ying; Xing, Hui; Wang, Zheng; Shao, Yiming (Frontiers in Immunology, 2024)
Background: Long-term non-progressors (LTNPs) with HIV infection can naturally control viral replication for up to a decade without antiretroviral therapy (ART), but the underlying mechanisms of this phenomenon remain elusive.To investigate the relevant immune and inflammatory factors associated with this natural control mechanism, we collected plasma samples from 16 LTNPs, 14 untreated viral progressors (VPs), 17 successfully ART-treated patients (TPs), and 16 healthy controls (HCs). The OLINK immune response panel and inflammation panel were employed to detect critical proteins, and the plasmaneutralizing activity against a global panel of pseudoviruses was assessed using TZM-bl cells.Results: Between LTNPs and VPs, the combination of IL17C, IL18, DDX58, and NF2 contributed to discriminating LTNPs and VPs; IL18 and CCL25 were positively associated with CD4 + T cell counts but negatively correlated with viral load. Furthermore, CXCL9 and CXCL10 emerged as potential supplementary diagnostic markers for assessing the efficacy of antiretroviral therapy (ART). Finally, TNFRS9 displayed positive correlations with neutralization breadth and Geometry Median Titer (GMT) despite the lack of significant differences between LTNPs and VPs.In summary, this study identified a set of biomarkers in HIV-infected individuals at different disease stages. These markers constitute a potential network for immune balance regulation in HIV infection, which is related to the long-term control of HIV by LTNPs. It provides important clues for further exploring the immune regulatory mechanism of HIV.